Biopsychosocial Approach for Conservative Management of Abdominal Pregnancy in Previously Infertile Mother. (30th August 2022) - Indarti, Junita; Saroyo, Yudianto Budi; Anggraheni, Beta Andewi Resti; Widyatama, Andika
Abstract : Background. Abdominal pregnancy is a rare condition in which early termination is generally recommended. However, there are cases of abdominal pregnancies treated using expectant management with satisfactory outcomes. This management may be considered in special cases, such as previously infertile couples. Case. A case of a 27-year-old woman with infertility history complaining of vaginal bleeding was presented. Physical and ultrasound examination revealed an abdominal pregnancy with 18 weeks of gestation. Although she was ready to abort the pregnancy, she insisted to try expectant management for her pregnancy. Her baby was finally born at 25 weeks via laparotomy. Conclusion. Abdominal pregnancy is a rare and highly morbid form of ectopic pregnancy. It demands a skilled approach in management. A comprehensive and holistic approach is required to deliver the best outcome for the patient and her family.